China-Pakistan Economic Corridor (Cpec) And Land Acquisition: A Case Study Of Rashakai Economic Zone - Jawad Arshad; Dr. Sajjad Ali Khan; Dr. Abdul Shakoor; Dr. Ahmad Ali (Elementary Education Online, 2023)
Foreign direct investment (FDI) is often geared towards the attainment of a variety of goals such as employment generation, infrastructure development, technological advancement, human resource development and overall development. Empirical evidence concerning the relationship between FDI and development suggests that FDI may sometimes also exacerbate poverty and inequalities through adversely affecting the means of the livelihood of people. The proposed study is interested in exploring the effects of FDI and dispossession through a case study of the Rashakai Economic Zone, a special economic zone established under the ChinaPakistan Economic Corridor (CPEC) in Khyber Pakhtunkhwa province of Pakistan. The proposed research entails the collection of both primary as well as secondary data. While primary data will be collected through semi-structured interviews and focus group discussion, secondary data will be retrieved from secondary sources such as local and national newspapers, officials communiqués etc. Contrast to the official rhetoric which attempts to tout the Rashakai Economic Zone as an engine of growth on development, the proposed study adumbrates that the so-called Economic Zone has resulted in dispassion of the poor and the destitute from their lands, a resource upon which their livelihoods largely hinge. The implications of this for the inclusive development could turn out to be consequential in the long run. The findings suggest by way of concluding that FDI may sometimes also exacerbate poverty and inequalities through adversely affecting the livelihood of the poor.